Formulation of zinc foliar sprays for wheat grain biofortification: a review of current applications and future perspectives - Sánchez-Palacios, José Tonatiuh; Henry, David; Penrose, Beth; Bell, Richard (Frontiers in Plant Science, 2023)
Agronomic biofortification of wheat grain with zinc can improve the condition of about one billion people suffering from zinc (Zn) deficiency. However, with the challenge of cultivating high-yielding wheat varieties in Zn-deficient soils and the global need to produce higher-quality food that nourishes the growing population, innovation in the strategies to deliver Zn directly to plants will come into play. Consequently, existing foliar formulations will need further refinement to maintain the high agronomic productivity required in competitive global grain markets while meeting the dietary Zn intake levels recommended for humans. A new generation of foliar fertilisers that increase the amount of Zn assimilated in wheat plants and the translocation efficiency of Zn from leaves to grains can be a promising solution. Research on the efficacy of adjuvants and emerging nano-transporters relative to conventional Zn forms applied as foliar fertilisers to wheat has expanded rapidly in recent years. This review scopes the range of evidence available in the literature regarding the biofortification of bread wheat (Triticum aestivum L.) resulting from foliar applications of conventional Zn forms, Zn nanoparticles and novel Zn-foliar formulations. We examine the foliar application strategies and the attained final concentration of grain Zn. We propose a conceptual model for the response of grain Zn biofortification of wheat to foliar Zn application rates. This review discusses some physiological aspects of transportation of foliarly applied Zn that need further investigation. Finally, we explore the prospects of engineering foliar nano-formulations that could effectively overcome the physicochemical barrier to delivering Zn to wheat grains.